THE PHENOMENON OF “BEING A MODEL” IN THE HISTORY OF HUMAN THOUGHT. - Лаврик, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article considers historical alternatives of judgement about the role and place of “being a model” phenomenon in the life of a human and society.